Do Grass and Legume Cover Crops Improve Soil Properties in the Long Term?. Issue 4 (18th July 2019) - Blanco‐Canqui, Humberto; Jasa, Paul J.
Abstract : Cover crops (CCs) are generally perceived to improve soil properties, yet available research suggests that CC impacts, particularly on physical properties, can be inconsistent. Length of time after CC adoption and CC species such as grass and legume CCs could differently influence CC effects, but experimental data are few. This study quantified 12‐yr cumulative impacts of grass CCs including cereal rye ( Secale cereale L.) and grain sorghum [( Sorghum bicolor (L.) Moench] and legume CCs including Austrian winter peas ( Pisum sativum L.) and soybean ( Glycine max L.) CCs on soil physical and fertility properties under long‐term (∼30 yr) continuous no‐till corn ( Zea mays L.)–soybean–winter wheat ( Triticum aestivum L.) rotation on a silty clay loam in the western Corn Belt. Legume CCs did not alter soil properties, but grass CCs improved soil aggregation and increased organic matter concentration although water infiltration, water retention, plant available water, and most soil fertility properties were unaffected. Grass CCs increased the proportion of large water‐stable aggregates (2–8.0 mm) by 31 to 45% in the 0‐ to 15‐cm depth. Grass CCs also increased mean weight diameter of water‐stable aggregates by 34% and organic matter concentration by 11% in the upper 7.5‐cm depth. Results indicate that grass CCs improved some soil properties unlike legume CCs. Long‐term (15 yr) no‐till use before CC adoption, fine texture, and high organic matter level of the soil may explain the small grass CC and no legume CC effects. Overall, grass CCs impacted some soil properties but legume CCs had no effects in this silty clay loam after 12 yr. Core Ideas: Legume cover crops (CCs) had no effects on soil properties after 12 yr. Grass CCs increased aggregation and organic matter but did not affect water infiltration, retention, and availability. Grass CCs had more impact on soil properties than legume CCs. Long‐term (15 yr) no‐till before CC adoption, fine texture, and relatively high soil organic matter may explain the small CC effects.